Influence of toxins in food on a little child's speech development - overview - Marta Wawrzynów (Kazimierz Wielki University, 2018)
Environmental toxicology is a well-known theme, but not every food toxicology "common" man had to deal with. Hearing the definition of "toxicology" we think that this is an area of medicine, but do not really know what it does and to what extent. Toxicology is the study of toxins, harmful effects on the impact on the health and life of a living organism. In these times it should be erected on a pedestal of medical science. The environment in which we live and lives is contaminated. Toxins are both in the inhaled by human air, of drinking water, food consumption, taking medication, inhaled (even by accident) the substances. There are many types of toxins. In this hearing, the importance will be those present in the food as: product additive, chemical, pesticide residues, mycotoxins, aflatoxins chloroprapanoli, amines, heavy metals, fungi, molds (manufactured improperly stored food or in bad conditions), and other xenoestrogens. The impact of toxins on children's development, and their speech to the 36th of the month is hypothesized to be relatively large. Children up to this moment (theoretically healthy, with normal development) are not subjected to specialist diagnosis, so they do not always small problems are seriously taken into account. It happens that parents or teachers of children (nursery, kindergarten) do not notice the difficulties, there are also often aware of them. The presence of toxins in the environment parents (before becoming pregnant women), prenatally and after birth to 36 months of age has a negative impact on child development.